Moldenhawera congestiflora: a new species of Leguminosae from the Brazilian Atlantic Forest - Vivas, Caio Vinicius; Souza, Gustavo; Amato Gaiotto, Fernanda; Paganucci De Queiroz, Luciano (Phytotaxa, 2019)
Moldenhawera is a small genus of Caesalpinioideae (Leguminosae), characterized by biramous (T-shaped) trichomes, compoundly pinnate stipules, hypanthium absence, clawed petals, dimorphic androecium, and anther connective of the fertile stamen pubescent. Moldenhawera congestiflora, a new species from the Atlantic Forest in Bahia State, Brazil is described and illustrated. It is distinguished from other species of the M. sect. Brasilianae by the combination of its tree habit, leaves relatively long (rachis > 24 cm long), leaflets elliptic to oblong with apex acuminate, flower buds densely grouped at the inflorescence apex, flowers pentamerous, petal blades relatively small (6–8 × 4–5 mm), and base of fertile stamen villous. Additionally we provide a new identification key for the section Brasilianae.